Implementation of ISMUBA Curriculum Development at SMA Muhammadiyah 23 Jakarta - Dafidt Firmansyah; Muhammad Abdullah Darraz (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research provides an explanation of how the Ismuba curriculum is applied in high school. This study uses a descriptive qualitative approach, describing various conditions in the field related to the teaching of Islam in Muhammadiyah 23 High School in Jakarta. This data source consists of an ismuba teacher who supports subjects, a number of other subject teachers and school principals. According to the results of the study, the Ismuba curriculum was used well in Muhammadiyah 23 High School in Jakarta. The Ismuba curriculum has been adapted to the Muhammadiyah Dikdasmen and included in the Religious School Curriculum. One of the shortcomings of the Ismuba curriculum in the Muhammadiyah 23 High School Education Unit in Jakarta is the lack of continuous teachers and unstable learning time allocation.